-9x + 7 = 3x + 19
Subtract 7 on each side...
-9x = 3x + 12
Subtract 3 on each side...
-12x = +12
Divide by -12 on each side...
x = -1
2006-11-14 09:22:30
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Add 9x to both sides: 7 = 3x + 9x + 19. Then subtract 19 from both sides: 7 - 19 = 3x + 9x. Then combine the terms: -12 = 12x. Finally, divide by 12: -1 = x.
2006-11-14 09:22:15
·
answer #2
·
answered by Amy F 5
·
1⤊
0⤋
First add 9x to both sides to remove x from side 1
7 = 12x + 19
then minus 19 from both sides to remove numbers from side 2
-12 = 12x
Therefore
x = -1
2006-11-14 09:22:39
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
-9x + 7 = 3x + 19
-12x + 7 = 19 ... subtract 3x from both sides
-12x = 12 ... subtract 7 from both sides
x = -1 ... divide both sides by -12
2006-11-14 09:21:38
·
answer #4
·
answered by Anonymous
·
2⤊
1⤋
-9x +7 = 3x + 19
-9x-3x=19-7
-12x=12
x=-1
2006-11-14 09:21:27
·
answer #5
·
answered by yupchagee 7
·
2⤊
1⤋
x = -1
2006-11-14 09:25:09
·
answer #6
·
answered by sri k 2
·
1⤊
0⤋
Subtract 3x on both sides:
-12x+7=19
Subtract 7 on both sides:
-12x=12
x=-1
Check:
-9(-1)+7=3(-1)+19
9+7=-3+19
16=16
2006-11-14 09:26:25
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
-9x+7=3x+19
-9x-3x=19-7
-12x=12
x=12/-12
x=-1
2006-11-14 09:21:44
·
answer #8
·
answered by Allieway 3
·
2⤊
0⤋
x=-2
2006-11-14 09:20:41
·
answer #9
·
answered by moonfreak♦ 5
·
0⤊
4⤋
x= -1
get like terms on the same side...when you do this you have -12x=12. divide both sides by -12, x= -1
2006-11-14 09:20:50
·
answer #10
·
answered by Honey Bear 2
·
2⤊
1⤋